Analysis Of The Use Of Electronic Medical Records With The Fishbone Method Approach At Rokan Hulu General Hospital - Maulana, David; Trisna, Wen Via; Sari, Tri Purnama (Universitas Muhammadiyah Sidoarjo, 2024)
RSUD Rokan Hulu has started implementing electronic medical records (RME) since September 2023 in outpatient services. RSUD Rokan Hulu provides 20 Polyclinics, of which 6 Polyclinics have implemented RME and 14 Polyclinics have not implemented RME. In its implementation, of course, it has obstacles. This study aims to determine the inhibiting factors for the use of electronic medical records based on the Man, Machine, Material, Method, Money factors. The type of research used is descriptive qualitative. The subjects in this study were the head of the medical record installation, nurses, doctors, IT / IMRS staff and KASI Humas. The object of this research is electronic Medical Records at Rokan Hulu Hospital, the methods used are interviews and observations. Data analysis uses descriptive analysis and the results are presented using a fishbone diagram. The results of inhibiting factors in the use of electronic medical records with the fishbone method approach at Rokan Hulu Hospital in 2024 based on the Man factor, namely the lack of special training in the use of RME to health workers, the limitations of health workers in using computers, and not all doctors want to use RME. The machine factor is the unavailability of electronic pens. Network material factors often experience interference and the RME application used is not easy for doctors to use. The method factor is that there is no SOP related to the use of RME and there are no guidelines for the flow of RME implementation. The money factor has no problems and obstacles.